EVALUATION OF THE SAMPLING DESIGN ADOPTED BY THE CENTRAL MARINE FISHERIES RESEARCH INSTITUTE FOR ESTIMATING MARfNE FISH PRODUCTION OF INDIA - Kutty, M Krishnan; Nair, A K Kesavan; Quasim, S Z (Indian Journal of Fisheries, 2011)
The sampling design used by the Central Marine Fisheries Research Institute, forcollecting the catch data of sea fish in India is based on the procedure of stratificationin space and time. The coastline is divided into different zones and one zone and acluster of 10 days are taken as the sizes of a space-time stratum. Generally one surveystaff is allotted to each zone. Certain limitations in the sampling system seem atpresent inevitable because of the fishing conditions under which the survey work is beingcarried out.